Fuzzy Algorithm and Air Quality Ranking—Taking 18 Urban Cities in China as an Example - Yu, Kui (Water, air, and soil pollution, 2023)
The air quality is generally graded into five levels in a simple way or released by the Air Pollution Index (API) which does not take the fine particulate matter (PM 2.5 ) emission into account. The fuzzy algorithm in this paper solves the mutability aroused by the grading approach by counting in the six items of pollutants pertaining to Short-lived climate forcers (SLCFs). Firstly, six items of air pollutants as well as driving factors of human activities are introduced. Secondly, based on the relevant observation data from the China Air Quality Online Monitoring Platform (CAQOMP), 18 experimental cities covering North China, East China, Central China, and South China are selected in this paper for air quality comparison and analysis in the application of the fuzzy algorithm. Thirdly, this paper looks into the air quality ranking of experimental 18 cities from a regional perspective. North China’s air quality is not optimistic owing to being in a location near the coal producer and sand-sourced Outer Mongolia. Central China’s air quality is more impacted by high-speed economic development and urbanization during the last couple of years. O 3 emission is not well controlled across China. It turns out that the ranking by using the fuzzy algorithmic method is more scientific and holistic than API.